PENGARUH LINGKUNGAN BISNIS DAN STRATEGI OPERASI TERHADAP KINERJA OPERASIONAL PADA UKM KERAJINAN GERABAH KASONGAN BANTUL - Ign. Sony Kurniawan; Risal Rinofah (LP2M Universitas Sarjanawiyata Tamansiswa, 2016)
This objective of the research was to examine whether or not the operations strategy mediate a relationship between business environment and operational performance. The research collected a sample of SMEs located in Kasongan Bantul Yogyakarta. The sampling was conducted by applying a non-probability method with a purposive sampling technique. The questionnaires processed were 70 in number, which were obtained from direct survey. The data collected were then analyzed by using a path analysis technique. The result of the research not proved that the operations strategy mediated a relationship between business environment and operational performance, but the business environment directly influence the operational performance.Â Key words: business environment, operations strategy, operational performance